Farelo da semente de maracujá na alimentação de suínos (30-90 kg) - Perondi, Dani (2013)
Two experiments were carried to determine the nutritional value and evaluate the performance of growing and finishing pigs fed diets with passion fruit seed meal (PSM). In experiment I, a digestibility trial with 30 crossbred pigs (36.85 ± 4.19 kg) was conducted, being 24 pigs for the test diets and 6 for the reference diet, distributed into a randomized block design. The replacement levels of basal diet for PSM were 4%, 8%, 12% and 16%. The experimental unit consisted of a pig, in a total of six experimental units per treatment. The values of the digestible (DE) and metabolizable energy (ME) of the PSM were estimated by linear regression analysis of DE and ME (kcal) intake associated with the PSM vs. PSM intake (kg). The values of DE and ME (kcal / kg), in the natural matter, were 3,244 and 3,223 kcal / kg, respectively. In experiment II, 75 pigs were used with initial and final body weight of 30.63 ± 1.49 and 60.38 ± 4.75 kg in the growing phase and 75 pigs with initial and final body weight of 60.40 ± 1.50 and 90.02 ± 4.84 kg in the finishing phase, alloted in randomized block design, with four levels of PSM inclusion levels (4%, 8%, 12% and 16%), with 15 repetitions and one pig per experimental unit. Additionally, a control diet was formulated, not containing PSM (0%). At the end of the finishing phase, all pigs were slaughtered to evaluate the quantitative carcass traits and meat quality. There was no effect (P>0.05) of the PSM inclusion on the daily feed intake, average daily gain, feed conversion, backfat depth and loin depth in the growing and finishing phases, and also on the quantitative carcass and qualitative meat traits in the finishing phase. There was no effect (P>0.05) of the PSM inclusion on the plasma variables in pigs in the finishing phase. However, in the growing phase, a linear increase (P≤0.05) of the cholesterol was found. The economic feasible indicated the possibility of using PSM up to 16% in diets for pigs in the growing and finishing phases. The results indicate that it is viable to utilize up to 16% of PSM to feed pigs (30-90 kg), with no effect on performance, plasma variables, quantitative carcass traits, meat quality and with the possibility of reducing the cost of food.